Realisasi Ajaran Teologi Sosial Melalui Tradisi Ngejot di Masa Pandemi Covid-19 - I Wayan Sunampan Putra (Sphatika: Jurnal Teologi, 2021)
Harmony in religious life is an important phenomenon to note. Considering that several different religions have developed in Indonesia, it is necessary to apply the teachings of harmony theology. Community life under religious pluralism is not always harmonious. In daily life, several cases of disharmony of religious communities often occur. This disharmony occurs because of the lack of tolerance between religious people with one another. To bring back the attitude of tolerance, one needs to explore religious teachings. Thus, there is no longer a nerrow mind against Hindus. The theology of harmony in the Hindu perspective in this case seeks to provide teachings about the unity of mankind. In the Hindu perspective of harmony theology, every human being should respect his fellow human beings because they come from the same source, namely God. Harmony is a religious obligation and obedience to God, it is also a cultural guideline and customs. The synergy between the two has always greatly influenced people's perspectives and attitudes regarding various matters, including efforts to create a harmonious life in the midst of plurality.